Comparative analysis of models (Altman, Grover, Zmijewski, Springate) in predicting company bankruptcy potential in the non-cyclical consumer sector - Kembi, Luke David; Morasa, Jenny; Wokas, Heince R. N, (Yayasan Widyantara Nawasena Raharja, 2024)
This research aims to conduct a comparative analysis of models (Altman, Grover, Zmijewski, Springate) in predicting potential bankruptcy for companies in the non-cyclical consumer sector listed on the IDX in 2020-2022. The main aim of this research is to test the results of the comparison of four models and test the accuracy of the prediction model in predicting bankruptcy. The data in this research is 240 data, namely 3 years of timeseries data and 80 companies using purposive sampling techniques according to certain criteria. Data analysis used the Kruskal Wallis Difference Test and Accuracy Level Test. The research results show that the Altman, Grover, Zmijewski, and Springate models have significant differences in results in predicting bankruptcy and the accuracy level test produces the Grover model with the best level of accuracy in predicting bankruptcy in non-cyclical consumer sector companies in 2020-2022.